2017
DOI: 10.3310/hta21200
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised trial, cost-effectiveness analysis and psychosocial evaluation of insulin pump therapy compared with multiple injections during flexible intensive insulin therapy for type 1 diabetes: the REPOSE Trial

Abstract: This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).Editorial contact: journals.library@nihr.ac.ukThe full HTA archive is freely available to view online at www.journalslibrary.nihr.ac.uk/hta. Print-on-demand copies can be purchased from the report pages of the NIHR Journals Library website: www.journalslibrary.nihr.ac.uk Criteria for inclusion in the Health Technology Assessment journalReports are published in Health Technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 139 publications
(223 reference statements)
3
66
0
1
Order By: Relevance
“…The Relative Effectiveness of Pumps Over MDI and Structured Education (REPOSE) trial found that among nonpregnant adults with poorly controlled T1D (HbA 1c .7.5% or 58 mmol/mol) and no preference for pumps or MDI, both groups had improved glycemic control following diabetes self-management education (27). The REPOSE trial also reported greater improvement in diabetes treatment satisfaction and some quality of life measures, including increased dietary freedom and decreased daily hassles among pump users (28). Since CONCEPTT participants were not randomized to pump or MDI and had experienced these insulin delivery methods before enrollment, it is not surprising that overall change in patient-reported outcomes did not differ in CONCEPTT.…”
Section: Discussionmentioning
confidence: 94%
“…The Relative Effectiveness of Pumps Over MDI and Structured Education (REPOSE) trial found that among nonpregnant adults with poorly controlled T1D (HbA 1c .7.5% or 58 mmol/mol) and no preference for pumps or MDI, both groups had improved glycemic control following diabetes self-management education (27). The REPOSE trial also reported greater improvement in diabetes treatment satisfaction and some quality of life measures, including increased dietary freedom and decreased daily hassles among pump users (28). Since CONCEPTT participants were not randomized to pump or MDI and had experienced these insulin delivery methods before enrollment, it is not surprising that overall change in patient-reported outcomes did not differ in CONCEPTT.…”
Section: Discussionmentioning
confidence: 94%
“…Studies report an improvement in glycemic control with the use of insulin, but worsening in patients' QoL (30). In addition, studies report an improvement in QoL (satisfaction with treatment) and symptoms of hypoglycemia in patients using an insulin infusion pump compared to those using multiple doses of insulin (three to four times a day) (31). The use of devices for continuous infusion of insulin was studied as an alternative to improve adherence to treatment and metabolic control.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the impact of CGM and insulin pump use on FOH is limited, although more studies have focused on CGMs. In general, research on the impact of CGMs on FOH is mixed [41] with several studies reporting no impact of CGM [37, 42] or insulin pump [43] use on FOH. In contrast, the STAR3 study of children and adults with T1D showed significant improvement in FOH when comparing the period of time prior to sensor-augmented pump initiation and the period following initiation [44].…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%